EXPLORING THE IMPACT OF COGNITIVE, AFFECTIVE, AND PERSONALITY DIFFERENCES ON LEARNING PROCESSES - Qalandarova Sabohat Atabekovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Individual differences play a critical role in shaping how learners engage with and internalize new information during various stages of the learning process. This study investigates the extent to which cognitive, affective, and personality-related individual differences predict distinct learning processes—namely encoding, rehearsal, elaboration, and metacognitive regulation. Employing a mixed-methods design, 180 undergraduate participants completed standardized measures of working memory capacity, cognitive style, learning motivation, and trait anxiety. Quantitative data were analyzed using structural equation modeling to examine direct and indirect effects of individual differences on learning outcomes. Complementing this, think-aloud protocols from a purposive subsample of 30 students were thematically coded to identify strategy use during problem-solving tasks. Results reveal that (a) higher working memory capacity and reflective cognitive styles are positively associated with deeper elaboration strategies, (b) intrinsic motivation and low anxiety levels predict more frequent metacognitive monitoring and regulation, and (c) personality traits linked to conscientiousness moderate the relationship between cognitive style and rehearsal strategies. Qualitative themes illustrate how learners adapt their study tactics in real time, confirming and extending the quantitative model. These findings underscore the necessity of tailoring instructional design to accommodate multidimensional individual differences, suggesting that adaptive scaffolding and metacognitive prompts can enhance learning efficiency. Implications for educators include integrating diagnostic assessments of learner profiles and embedding process- oriented interventions to foster self-regulated learning.